A Regenerative Antioxidant Protocol of Vitamin E and α-Lipoic Acid Ameliorates Cardiovascular and Metabolic Changes in Fructose-Fed Rats. (9th March 2011) - Patel, Jatin; Matnor, Nur Azim; Iyer, Abishek; Brown, Lindsay
Abstract : Type 2 diabetes is a major cause of cardiovascular disease. We have determined whether the metabolic and cardiovascular changes induced by a diet high in fructose in young adult male Wistar rats could be prevented or reversed by chronic intervention with natural antioxidants. We administered a regenerative antioxidant protocol using two natural compounds: α-lipoic acid together with vitamin E (α-tocopherol alone or a tocotrienol-rich fraction), given as either a prevention or reversal protocol in the food. These rats developed glucose intolerance, hypertension, and increased collagen deposition in the heart together with an increased ventricular stiffness. Treatment with a fixed combination of vitamin E (either α-tocopherol or tocotrienol-rich fraction, 0.84 g/kg food) and α-lipoic acid (1.6 g/kg food) normalized glucose tolerance, blood pressure, cardiac collagen deposition, and ventricular stiffness in both prevention and reversal protocols in these fructose-fed rats. These results suggest that adequate antioxidant therapy can both prevent and reverse the metabolic and cardiovascular damage in type 2 diabetes.